Security First: For a Muscular, Moral Foreign Policy by Amitai Etzioni (New Haven and London: Yale University Press, 2007. 308 pages.) (American Journal of Islam and Society, 2009)
Couched in moral language and endeavoring to preempt possible shifts inforeign policy attitudes, this six-part book attempts to subtly and indirectlyweave Israeli interests into American policy and upcoming decision-makingprocesses. Essentially, it repackages Israel’s “security for peace” formulawith the language of security (read “order”) and democracy (read “justice/law”) and stresses the former’s priority over the latter – security being Israel’sparamount claim. In so doing, Etzioni seeks to limit references to Israel togive the reader the impression that he is dealing with issues over and beyond– a form of reorienting the reader’s attention through focal deception while“playing the same tune – on a different instrument” (p. xii).The book’s main thesis is that there are “principled” and “pragmatic”reasons forWashington to transform its foreign policy approach from prioritizingthe spread of democracy to security (p. xi), for democracy must followthe establishment of “basic security” (p. xi) as the supreme human good.Doing things differently simply reflects the “Multiple Realism DeficiencyDisorder” from which American foreign policy suffers (p. xiv), namely, apsychological state that deals with matters as Americans would like them tobe rather than as they are (p. xv) ...